2004
DOI: 10.1051/0004-6361:20040414
|View full text |Cite
|
Sign up to set email alerts
|

Initial mass function in the South-Western part of M 31

Abstract: Abstract.We derive an average initial mass function (IMF) for 50 OB associations in the South-Western part of Andromeda galaxy, combining ultraviolet photometry of Hill et al. (1995, ApJ, 98, 595) and two datasets HST photometry with JHK s photometry from the 2MASS + I band photometry from Magnier et al. (1992, A&A, 96, 379). The mean extinctions within the associations were estimated in two independent ways and the stellar masses were determined by use of probabilistic techniques. The derived slope of the IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Using a framework to infer the distribution of mass function slopes given a set of noisy measurements (Hogg et al 2010;Foreman-Mackey et al 2014), they find that the high mass slope of the IMF is best described by α h = −2.45 +0.06 −0.03 , somewhat steeper than the high mass slope of Kroupa (2001) Andrews et al (2014). This is similar to the result of Veltchev et al (2004) who found α h = −2.59 ± 0.09 (for m > ∼ 7 M ⊙ ) using colour-magnitude diagrams for 50 OB associations in the south-western region of M31.…”
Section: Stellar Clustersmentioning
confidence: 63%
“…Using a framework to infer the distribution of mass function slopes given a set of noisy measurements (Hogg et al 2010;Foreman-Mackey et al 2014), they find that the high mass slope of the IMF is best described by α h = −2.45 +0.06 −0.03 , somewhat steeper than the high mass slope of Kroupa (2001) Andrews et al (2014). This is similar to the result of Veltchev et al (2004) who found α h = −2.59 ± 0.09 (for m > ∼ 7 M ⊙ ) using colour-magnitude diagrams for 50 OB associations in the south-western region of M31.…”
Section: Stellar Clustersmentioning
confidence: 63%
“…Fifty OB associations summed together in M31 were found to have an IMF slope of À2:59 AE 0:09, using a combination of space-based UV and HST photometry, Two Micron All Sky Survey (2MASS) photometry at the JHK bands, and I-band photometry ( Veltchev et al 2004). The stellar masses ranged from 8 to 100 M .…”
Section: Observations Of Galaxy-integrated Imfsmentioning
confidence: 99%
“…In addition, there are practical problems with star counts in external galaxies, including crowding, incompleteness, and corrections for foreground stars. Among other studies, Veltchev et al (2004) studied the IMF of M 31 and derived a slope of γ = −2.59 ± 0.09; Jamet et al (2004) found an IMF slope of γ = −2.37 ± 0.16 for the ionizing cluster of NGC 588 in the outskirts of the nearby galaxy M 33; Annibali et al (2003) analyzed the star formation history of NGC 1705 and inferred an IMF slope close to Salpeter.…”
Section: The Imf Of the Resolved Populationmentioning
confidence: 99%
“…OB associations have been discovered in some Local Group galaxies, and with the fine spatial resolution provided by the HST, it is possible to obtain the stellar IMF of those systems. Recent works include M31 (Veltchev et al 2004), M33 (González Delgado & Pérez 2000), IC10 (Hunter 2001), and IC1613 (Georgiev et al 1999). The previous work on the IMF of NGC 4214 has been based on the integrated spectrum of the galaxy (Leitherer et al 1996;Chandar et al 2005).…”
Section: Introductionmentioning
confidence: 99%